Falling short or rising above the fray? Rising powers and security force assistance to Africa - Seabra, P. (Journal of Intervention and Statebuilding, 2021)
Despite an increase in rising powers providing security force assistance (SFA) to Africa, the expertise and the capabilities made available by these countries remain insufficiently explored. What different solutions, if any, are brought forward? And how does their overall record fare against previous experiences across the continent? By exploring Brazilian and Chinese efforts in Namibia as well as Chinese and Indian overtures towards Mozambique, I argue that rising powers tend to be more invested in a long-term socializing agenda than in immediate capacitation results. This, in turn, justifies their inroads in sectorial niches, as gateways for durable outcomes over time.